From Cash to Clicks: A Systematic Review on the Role of Digital Payment Systems in Enhancing MSMEs' Competitiveness and Financial Inclusion - Hermawan, Muhammad Distian Andi; Septiani, Debi (Publication Division of International Ecsis Association, 2025)
The rapid shift from cash-based transactions to digital payment systems has transformed the operational practices of Micro, Small, and Medium Enterprises (MSMEs), particularly in emerging economies such as Indonesia. Despite increasing adoption of digital payment platforms, empirical evidence on their effectiveness in enhancing MSME competitiveness and financial inclusion remains dispersed and inconclusive. The research employs a Systematic Literature Review (SLR) approach encompassing the stages of planning, conducting, and reporting the review. Literature searches were conducted across four major academic databases Scopus, ScienceDirect, Google Scholar, and DOAJ to identify peer-reviewed articles published between 2017 and 2024. Data were analyzed using thematic content analysis to extract key themes related to digital payment adoption drivers, barriers, and impacts on MSME performance. The results demonstrate that digital payment adoption—particularly QRIS, e-wallets, and mobile banking—enhances MSME competitiveness by improving transaction efficiency, expanding market reach, and strengthening financial record management. In addition, digital payment usage supports financial inclusion by creating transaction histories that facilitate access to formal financial services, credit evaluation, and financing opportunities. The findings imply that the effectiveness of digital payments depends not only on technological availability but also on supportive policies, digital and financial literacy programs, and inclusive digital infrastructure. This study contributes to the literature by providing a structured and PRISMA-based synthesis of existing evidence, clarifying the conceptual link between digital payments, MSME competitiveness, and financial inclusion, while identifying critical gaps for future empirical research.